Respuesta :
Answer:
[tex](a+b)^2=a^2+2ab+b^2[/tex]
Step-by-step explanation:
We have been given an incomplete statement [tex](a+b)^2=a?+b^2[/tex]. We are supposed to complete the given statement.
We can see that left side of our given equation represents a perfect square. The right side of equation would be perfect square trinomial.
Let us use perfect square formula to expand our given perfect square as:
[tex](x+y)^2=x^2+2xy+y^2[/tex]
Substitute [tex]x=a[/tex] and [tex]y=b[/tex]:
[tex](a+b)^2=a^2+2ab+b^2[/tex]
Therefore, the complete statement would be [tex](a+b)^2=a^2+2ab+b^2[/tex].